El marco de la enseñanza para la comprensión aplicado al aprendizaje de la Historia y su relación con las realidades de los estudiantes de quinto grado del Colegio Interamericano (2014)
This is an intervention project within the framework or qualitative research, which realizes the process that took place in the Interamericano School with Fifth grade students of the Basic Primary, which from a descriptive methodology addresses history to reality.